ABOUT MOVEMENT OF THE SATELLITE OF THE GROUND AROUND OF THE GROUND - Katekov, Ye. (Recent Contributions to Physics, 2011)
In article three-dimensional spatial curves are stated. Among them frequently meeting - a trajectory of the satellite of the ground. The satellite rotates around of the ground and together with the ground rotates around of the sun. In article the equation of movement of the satellite and the formula on which the length of its way is calculated is resulted.
Keywords: three-dimensional spatial curves; trajectory of the satellite